2013
DOI: 10.5114/pjp.2013.34599
|View full text |Cite
|
Sign up to set email alerts
|

A cocktail of MCM2 and TOP2A, p16 INK4a and Ki-67 as biomarkers for the improved diagnosis of cervical intraepithelial lesion

Abstract: The purpose of this paper was to explore the immunohistochemistry (IHC) results for a cocktail of minichromosome maintenance protein 2 (MCM2) and topoisomerase IIα (TOP2A), p16 INK4a and Ki-67 as biomarkers for the diagnosis of cervical intraepithelial neoplasia (CIN), improving the routine interpretation of cervical histopathology. 133 cases of CIN were collected from the archival data. All routine hematoxylin and eosin (HE)-stained slides of the subjects were re-examined independently by three senior patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Our results show that TOP2A and RFC4 play an important role in this process. TOP2A is regarded as a biomarker for the improved diagnosis of CIN 26 . Recent study has shown that TOP2A protein is expressed in cells with aberrant S-phases and including HPV-transformed cells in association with elevated expression of the HPV E6/E7 proteins 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that TOP2A and RFC4 play an important role in this process. TOP2A is regarded as a biomarker for the improved diagnosis of CIN 26 . Recent study has shown that TOP2A protein is expressed in cells with aberrant S-phases and including HPV-transformed cells in association with elevated expression of the HPV E6/E7 proteins 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent study has shown that TOP2A protein is expressed in cells with aberrant S-phases and including HPV-transformed cells in association with elevated expression of the HPV E6/E7 proteins 27 . It is worth noting that many studies have shown that TOP2A expression level is significantly correlated with CIN grade 26,28 . In addition, RFC4 accelerated G1 to S phase progression, and promoted the proliferation of cervical cancer cells and the growth of cervical cancer 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that overexpression of MCM2 can be utilized to increase the diagnosis of CIN and squamous cell carcinoma (SCC) 16 , 17 . Moreover, a cocktail of MCM2 and TOP2A , p16INK4 and Ki-67 has been suggested as biomarkers for better diagnosis of CIN lesion 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Several tumor-type criteria for PI establishment have been elaborated. Digital image analysis systems can further improve the reliability of PI assessment [1,13,26].…”
Section: Discussionmentioning
confidence: 99%
“…In adult cancers, such as neuroendocrine tumors, breast carcinoma, lymphomas, prostate cancer and gliomas, the Ki-67 labeling index is included in the routine diagnostics, having therapeutic implications [1,2,27]. Likewise, the assessment of topoisomerase II alpha (Topo2A) expression emerges as a prolifera-tion marker in several cancer types, including brain tumors [12,26,29]. Ki-67 nuclear protein is required for maintaining cell proliferation, as it is detectable in all active phases of the cell cycle (G1, S, G2 and M) but absent in the resting phase G0 [21,28].…”
Section: Introductionmentioning
confidence: 99%